Conduction system pacing using electro-anatomical mapping-guided system vs. fluoroscopy: a systematic review, meta-analysis and economic evaluation - León-Salas, Beatriz; Infante-Ventura, Diego; Hernández-Yumar, Aránzazu; Linertová, Renata; Herrera-Ramos, Estefanía; Torres-Castaño, Alezandra; González-Pacheco, Himar; Abt-Sacks, Analía; García-García, Javier; Quirós-López, Raúl; Trujillo-Martín, María M. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionElectro-anatomical mapping (EAM) system has been shown as an alternative procedure to fluoroscopy for conduction system pacing (CSP) in patients with severe bradyarrhythmia, however its beneficial and harmful effects has not been assessed in a systematic review (SR). We sought to assess their safety, effectiveness and cost-effectiveness.MethodsA SR of the available scientific literature was conducted on the safety, effectiveness, and cost-effectiveness of CSP using EAM system versus fluoroscopy in patients with severe bradyarrhythmia. A partial economic evaluation was carried out to compare the costs of both strategies from the perspective of the Spanish National Health System. A budget impact analysis was also conducted with a five-year horizon.ResultsSeven comparative observational studies (N = 231), analyzing the use of EAM versus fluoroscopy were selected. Statistically significant differences were observed in total fluoroscopy time: −9.87 minutes (95%CI:−14.20, −5.53, p < 0.01; I2 = 95%; k = 7; n = 231); His-lead fluoroscopic time: −8.08 minutes (95%CI:−10.36, −5.81, p < 0.01; I2 = 0%; k = 2; n = 50); and His-lead radiation dose: −17.21 mGy (95%CI:−24.08, −10.34, p < 0.01; k = 1; n = 20). No differences in total fluoroscopy dose, successful procedure or safety were found. The use of EAM represents an increase of EUR 1397.81 per patient and a net budget impact of EUR 1.63 million.DiscussionEAM is a valuable alternative for patients who should not be exposed to ionizing radiation with similar effectiveness and safety than fluoroscopy. However, the inclusion of EAM systems, for the indication under study, in routine clinical practice would mean an increase in costs for the Spanish National Health System.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=421072, identifier (CRD42023421072).